Influence of Al Alloying on the Electrochemical Behavior of Zn Electrodes for Zn–Air Batteries With Neutral Sodium Chloride Electrolyte - Durmus, Yasin Emre; Montiel Guerrero, Saul Said; Tempel, Hermann; Hausen, Florian; Kungl, Hans; Eichel, Rüdiger-A. (Frontiers in Chemistry, 2019)
Zn alloy electrodes containing 10 wt. % Al were prepared to examine the applicability as anodes in primary Zn–air batteries with neutral 2M NaCl electrolyte. These electrodes were investigated by electrochemical measurements and microscopic techniques (SEM, LSM, AFM). Based on the cyclic voltammetry and intermediate term (24 h) discharge experiments, the only active element in the as-prepared alloy was found to be Zn. It was further confirmed by LSM that Zn rich areas dissolved while Al remained passive during discharge. The passive state of Al was also demonstrated by conductive AFM investigations on the as-cast alloy surfaces. The results on potentiodynamic polarization and weight loss measurements indicated that the alloy electrode was less prone to corrosion than pure Zn electrode. The electrochemical behavior of the electrodes was modified under certain cathodic polarization previous to measurements. Accordingly, originating from Al activation due to application of cathodic potentials, potentiodynamic polarization studies showed a clear shift on the corrosion potentials of the alloy toward more negative values. On the basis of these results, with the precondition of Al activation prior to discharge experiments, the effect of Al alloying on the Zn electrodes was revealed as temporarily enhanced potentials on the discharge profiles in comparison to pure Zn electrodes.